2016
DOI: 10.3109/15622975.2016.1155746
|View full text |Cite
|
Sign up to set email alerts
|

C-reactive protein: A differential biomarker for major depressive disorder and bipolar II disorder

Abstract: Objectives We aimed to examine whether the C-reactive protein (CRP) level could be used to differentiate between major depressive disorder (MDD) and bipolar II disorder (BD II). Methods Ninety-six healthy controls, 88 BD II and 72 MDD drug-naïve patients in their major depressive episodes were enrolled. The fasting plasma level of high-sensitivity CRP was assessed at baseline and after treatment. Results The BD II patients presented significantly higher 17-item Hamilton Depression Rating Scale (HDRS) scores an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 48 publications
2
39
0
Order By: Relevance
“…BD patients show lower levels of plasma TNF-a and IL-13 (111), and serum IL-1b (112) compared to MDD patients. On the other hand, BD patients presented higher Creactive protein, sTNFR1, soluble IL-6 receptor (sIL-6R), and MCP-1 levels compared to MDD patients (33,113). Another group has tried to investigate the difference in the peripheral inflammatory markers' levels between BD illness phase.…”
Section: Immune Markers As Clinical Outcome and Diagnostic Predictorsmentioning
confidence: 99%
“…BD patients show lower levels of plasma TNF-a and IL-13 (111), and serum IL-1b (112) compared to MDD patients. On the other hand, BD patients presented higher Creactive protein, sTNFR1, soluble IL-6 receptor (sIL-6R), and MCP-1 levels compared to MDD patients (33,113). Another group has tried to investigate the difference in the peripheral inflammatory markers' levels between BD illness phase.…”
Section: Immune Markers As Clinical Outcome and Diagnostic Predictorsmentioning
confidence: 99%
“…Recent meta-analyses have found decreased levels of kynurenine in MDD versus healthy controls but not in bipolar disorder [67]. Using high-sensitivity testing of fasting plasma CRP levels at baseline and after treatment, Chang and colleagues reported that a baseline CRP level of 621.6 ng/mL could discriminate between bipolar disorder II and MDD [68]. However, Powell et al found that reduced transcription of IL8 could be used to distinguish both MDD and bipolar disorder from control subjects [69].…”
Section: Relationship Between Pro-inflammatory Cytokines and The Braimentioning
confidence: 99%
“…It is of clinical importance regarding the high prevalence of metabolic disturbance in BD patients (Chang et al, 2009b;Hung Chi et al, 2013;Vancampfort et al, 2013). CRP plays a pivotal role in aspects of inflammation that appears to be related to BD across several important domains (Chang et al, 2016;Goldstein et al, 2009;Leboyer et al, 2012a). Moreover, inflammation has been proposed to be the underlying mechanism that links BD and metabolic disturbances (Kim et al, 2007;Leboyer et al, 2012a;Lee et al, 2013a), as a previous study revealed apparent metabolic disturbances in BD patients with high CRP levels (Tsai et al, 2014).…”
Section: Discussionmentioning
confidence: 99%